2009
DOI: 10.1002/cncr.24372
|View full text |Cite
|
Sign up to set email alerts
|

Making a link between childhood physical abuse and cancer

Abstract: BACKGROUND:Abuse in childhood is associated with many negative adult health outcomes. Only 1 study to date has found an association between childhood abuse and cancer. By using a regionally representative community sample, this preliminary study sought to investigate the association between childhood physical abuse and cancer while controlling for 3 clusters of risk factors: childhood stressors, adult health behaviors, and adult socioeconomic status.METHODS:Regional data from the Canadian provinces of Manitoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 51 publications
1
81
0
3
Order By: Relevance
“…Most of these studies have shown higher rates of poor physical health [24][25][26], obesity [18], anxiety and depression [27], personality disorders [28], aggression and attention deficithyperactivity disorder (ADHD) [29], substance use disorders [30], chronic conditions [31], and suicide-related behaviors [32,33] among adults with a history of childhood adversities.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have shown higher rates of poor physical health [24][25][26], obesity [18], anxiety and depression [27], personality disorders [28], aggression and attention deficithyperactivity disorder (ADHD) [29], substance use disorders [30], chronic conditions [31], and suicide-related behaviors [32,33] among adults with a history of childhood adversities.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Child maltreatment has also been linked to physical symptoms such as pain, physical health conditions including disability, poor or fair self-rated health, and frequent emergency department visits. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Infants experiencing frequent physical punishment have been shown to have high hormonal reactivity to stress. 25 It could be that children experience cumulative exposure to physical punishment as psychologically and physically stressful, which is the case for child maltreatment.…”
mentioning
confidence: 99%
“…Evidence has demonstrated links between childhood maltreatment and a range of illnesses in adulthood, such as fibromyalgia, irritable bowel syndrome, chronic lung disease and cancer (Fuller-Thomson and Brennenstuhl 2009;Gilbert 2009;Krug et al 2002). Perhaps the most prevalent of these health linkages -in both childhood and adulthood -is the relationship of child abuse and neglect to mental health conditions.…”
Section: Link Between Child Maltreatment and Mental Healthmentioning
confidence: 99%